Exploring the Impact of Self-Regulation on Role Conflict Among Students: Mengeksplorasi Dampak Regulasi Diri terhadap Konflik Peran di Kalangan Mahasiswa - Wulansari, Nindi; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative correlational study investigates the relationship between self-regulation and role conflict among organizational students at Muhammadiyah University of Sidoarjo. Using a sample of 169 students, the research reveals a significant negative correlation (rho = -0.452, p < 0.001) between self-regulation and role conflict, indicating that higher levels of self-regulation are associated with lower perceived conflict in balancing academic and organizational roles. The implications suggest promoting self-regulation as a strategy to reduce role conflict and enhance overall well-being among organizational students, contributing to theoretical knowledge and guiding future research in understanding psychological attributes related to role conflict comprehensively. Highlight: Correlation found: self-regulation and role conflict among organizational students. Self-regulation can reduce conflict balancing academic and organizational roles. Study contributes to understanding psychological aspects of role conflict. Keyword: Self-regulation, Role conflict, Organizational students, Quantitative correlational study, Muhammadiyah University.